Prevalence of Anisometropia and its Association with Stereopsis and Amblyopia Among School Children in the Goa. - Mulla, Rahufa; Usgaonkar, Ugam P. S.; Shetty, Aksha (Optometry & Visual Performance, 2023)
Background: To determine the prevalence of anisometropia and its association with stereopsis and amblyopia in Goan school children. Methods: A cross-sectional study was conducted on students between 9 and 14 years of age from two randomly selected schools in Goa. All students underwent an assessment of uncorrected and best-corrected visual acuity, stereo acuity, and complete ophthalmic examination. Children with refractive errors without any other coexisting ocular pathologies were included. Refractive correction of children with a best-corrected visual acuity of logMAR 0.0 was measured using a manual lensometer. Subjects with visual acuity greater than logMAR 0.2, further improving with pinhole, were subjected to objective and subjective refraction. The prevalence of anisometropia, anisometropic amblyopia, and degree of stereo acuity in anisometropic children was assessed. Results: Four hundred and six children were screened for refractive errors. Sixty-four children were found to have refractive errors, of which 58 students (90.6%) were myopic, and six (9.4%) were hyperopic. The prevalence of anisometropia of ≥1.0 D spherical equivalent was found in 12 students (18.75%), among whom myopia was the most common refractive error (9.75%). Anisometropic amblyopia was noted in eight students (66.6%), five of whom were myopes and three hyperopes. All three hyperopic anisometropes (100%) had amblyopia. Seventy-five percent of children with poor stereo acuity, ranging from ≥160 seconds of arc, belonged to the hyperopic anisometropia group. Conclusion: Amblyopia is more prevalent among anisometropes than isometropes, with hyperopic anisometropes having poor stereoacuity and being more likely to develop amblyopia. Hence, early identification and treatment of anisometropia will significantly reduce the risk of amblyopia in school children.